Production and Characterization of The Basic Soaps Obtained by Double Decomposition and Direct Process of Palm Stearin Oils. (June 2019) - Neonufa, G F; Pratiwi, M; Purwadi, R; Prakoso, T; Soerawidjaja, T H; Elizabeth, L
Abstract: The direct and double decomposition process of palm stearin oil were evaluated for the production of basic soaps as a decarboxylation feedstock to drop-in fuel produce. The metals proposed for the saponification reaction was magnesium which has a high-basicity and is a low-cost metal. The Fourier transform infrared spectroscopy profile of the Mg(OH)–stearin basic soaps obtained by both direct and double decomposition processes showed hydrocarbon groups such as alkanes and alkene, without the oxygenate groups. The basic soap products generated by the double decomposition process showed better basicity level which was determined based on the IR spectrum intensity, especially of the -OH group. The type of saponification process used in the resulted basic soaps can provide a different effect on the generated basic soaps characteristic.